2001
DOI: 10.1161/hc3201.092216
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Effect Afforded by Transient Exposure to Phosphodiesterase III Inhibitors

Abstract: Background-Phosphodiesterase III inhibitors (PDEIII-Is) improve the hemodynamic status of heart failure via inotropic/vasodilatory effects attributable to the increase in intracellular cAMP level. Direct cardioprotection by PDEIII-Is and its underlying mechanisms, however, have not been identified. We tested the infarct size-limiting effect of PDEIII-Is and the roles of cAMP, protein kinase (PK) A, PKC, and mitogen-activated protein kinase (MAPK) families in open-chest dogs. Methods and Results-Milrinone, olpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
79
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 44 publications
8
79
0
1
Order By: Relevance
“…[33] . However, when delivered at 1.35 μg/kg per minute in dogs or at 10 μmol/L in isolated rat hearts approximately 30 min before preconditioning, H-89 completely blunted the infarct-limitation effect of preconditioning [12,34] . Therefore, the partial inhibition of H-89 on SIM cardioprotection in our study most likely occurred because H-89 was delivered later than SIM, and the contradiction between these studies might be explained by the differences in H-89 dosage, experimental protocols, and animal species.…”
Section: Discussionmentioning
confidence: 94%
“…[33] . However, when delivered at 1.35 μg/kg per minute in dogs or at 10 μmol/L in isolated rat hearts approximately 30 min before preconditioning, H-89 completely blunted the infarct-limitation effect of preconditioning [12,34] . Therefore, the partial inhibition of H-89 on SIM cardioprotection in our study most likely occurred because H-89 was delivered later than SIM, and the contradiction between these studies might be explained by the differences in H-89 dosage, experimental protocols, and animal species.…”
Section: Discussionmentioning
confidence: 94%
“…Amrinone also improved contractile recovery after ischemia-reperfusion (IR) in the isolated rat heart in an extracellular calcium dependent manner [93] . Furthermore, injection of milrinone or olprinone before IR reduced infarct size in dogs [94] . Further dissection of the signaling pathways involved in olprinone-mediated protection revealed that it induced cardioprotection through cAMP/PKA and p38-MAPK dependent, but not PKC dependent mechanisms [94] .…”
Section: Phosphodiesterasementioning
confidence: 89%
“…Furthermore, injection of milrinone or olprinone before IR reduced infarct size in dogs [94] . Further dissection of the signaling pathways involved in olprinone-mediated protection revealed that it induced cardioprotection through cAMP/PKA and p38-MAPK dependent, but not PKC dependent mechanisms [94] . The authors proposed that the end-effectors of p38-MAPK may include opening of the mitochondrial ATP-sensitive potassium channel (mitoKATP) channel or translocation of Hsp27 to the Z-disc to stabilize the myofibril and cytoskeleton.…”
Section: Phosphodiesterasementioning
confidence: 89%
“…Improvement of myocardial pump function and myocardial damage will be the important strategies in this situation. Recent studies demonstrated that PDE III inhibitors attenuate myocardial damage and pump function after ischemia-reperfusion injury [9,12,13]. PDE III inhibitors are the therapeutic agents for acute congestive heart failure and they possess positive inotropic and vasodilatory action.…”
mentioning
confidence: 99%
“…They speculate that the reduction of Ca 2+ overload in the myocyte due to amrinone induces the myocardial cardioprotection. Also, Sanada et al reported that the transient activation of p38 MAPK which induced by PDE III inhibitors elicit cardioprotection [13]. However, the mechanisms of myocardial protection from ischemiareperfusion injury by PDE III inhibitors are not clarified.…”
mentioning
confidence: 99%